Perceptions and Challenges of Women in Islamic Banking Leadership in Asia - Amri Amrulloh; Yopie Diondy Kurniawan; Putri Octa Cahya Nirwana (SEULANGA SYSTEM PUBLISHER, 2024)
This study explores the perceptions and challenges faced by women in leadership roles within Islamic banks across Asia. Using a qualitative approach, in-depth interviews were conducted with female leaders in various Asian countries to examine their experiences and views on leadership in the Islamic financial industry. The findings reveal that, despite increasing female participation in leadership, significant barriers persist, including gender stereotypes, difficulties in balancing work and family life, and a lack of institutional support. These findings underscore the need for more inclusive strategies to empower women in leadership positions within the Islamic finance sector